Volume 4: Advanced Manufacturing Processes; Biomedical Engineering; Multiscale Mechanics of Biological Tissues; Sciences, Engin 2012
DOI: 10.1115/esda2012-82410
|View full text |Cite
|
Sign up to set email alerts
|

Design for Manufacture Using Functional Analysis and CAD Mould Simulation for Rapid Prototyping and Rapid Tooling

Abstract: The pressure of time, quality and cost, together with increasing product variety, more customised products and worldwide competition is driving technology development and implementation in the area of Rapid Manufacturing (RM). Traditionally, the manufacture of tooling for both prototype parts and production components represents one of the longest and most costly phases in the development of most new products. The cost and time implications of the tooling process are particularly problematic for low-volume pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, Karunakaran et al 21 stated that rapid tooling is still limited to manufacturing prototypes with generally non-metallic materials. Lupeanu et al 22 examined rapid tooling advantages when developing a highly complex surface feature of a mould and how it was difficult to manufacture using conventional machining technologies. Previous successful studies were reviewed by 23 for low volume production of injection mould tooling.…”
Section: Introductionmentioning
confidence: 99%
“…However, Karunakaran et al 21 stated that rapid tooling is still limited to manufacturing prototypes with generally non-metallic materials. Lupeanu et al 22 examined rapid tooling advantages when developing a highly complex surface feature of a mould and how it was difficult to manufacture using conventional machining technologies. Previous successful studies were reviewed by 23 for low volume production of injection mould tooling.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that Rapid Tooling (RT) is a technique with great potential that aims to significantly reduce the product development cycle [19,20], eventually yielding cost and time benefits [21]. Wohlers [16] indicated that AM should not be overlooked as a technology that can produce tools, with significant potential to produce tooling inserts.…”
Section: Introductionmentioning
confidence: 99%
“…The capability to provide a high quality, accurate, bespoke surgical products in a short period of time, is a key factor for introducing AM technologies in reconstructive surgery protocols [3,4,7]. Thus, surgical procedures will benefit on a much larger scale from the advantages that these technologies offer [3,4].…”
Section: Introductionmentioning
confidence: 99%